Assessing EFL Papuan students' ability in memorizing English vocabulary using context clues strategy - Gultom, Monika (Faculty of Languages, Arts, and Culture Universitas Negeri Yogyakarta, 2023)
Research on how to utilize students' ability to master the foreign language especially in memorizing some words in a target language is believed very important. The purpose of the study is to assess the ability of native Papuans in memorizing some English vocabulary using the keyword system strategy of a selected translated Sentani folktale, entitled The Legend of Sentani Lake. Data was obtained from around 32 students who were asked to memorize several target words. The result showed that students' keyword system strategy was useful in connecting the spelling, pronunciation, and new words to their prior knowledge by looking at the similarity between the target word and keyword in sound using the key-word system strategy. It is also showed that Papuan EFL students have a high ability to utilize existing knowledge and memorable relationship to memorize new or currently studied English vocabulary. The findings provide important insight for foreign language teaching and learning regarding the importance of encouraging students to develop their ability to master the language being learned by connecting it with something close to the context of Papuan native students' live in order to make it more effective and meaningful.